Rules of engagement: Improving teaching through online faculty development training - Gilzene-Cheese, Florence; Fleming-Banks, Phyllis; Drakes, Claudia; Gilzene, Sharon (My University, 2015)
Resourcing education is a challenge for tertiary institutions. In the Caribbean, some governments have reduced funding at this level. Institutions like The University of the West Indies (UWI) Open Campus, which offer distance education, have been exploring innovative and creative ways for contracting staff and improving engagement to meet these changing realities. The examination of the impact of training on online facilitators yields useful data for higher education institutions. The Open Campus employs only adjunct facilitators who are usually experts in their disciplines and have industry experience but, generally, are employed per semester (or as needed) and are not teacher-trained or prepared to deliver in the online environment. Curriculum training to understand how the course is aligned to the delivery strategies therefore assumes critical importance. This paper examines one faculty development pathway used in the Open Campus for preparatory training, by identifying the critical competencies for online teaching success and the impact of these on online facilitators. The perspectives of forty-six (46) new facilitators on the value of the training process, and the competencies and best practices gained from the engagement are reviewed. Data from an impact survey were validated through focus group interviews and periods of close observation. Themes emerging from the data include: access and motivation, socialization to the online environment; and knowledge construction and efficacy. These were also validated and refined through focus group interactions. Key findings are presented using an embedded mixed methods approach with supporting data from qualitative and quantitative paradigms. These data-sets are supported by relevant research literature. The findings suggest that structured training pathways for adjunct faculty yield positive results. Participants' perspectives indicate viable strategies and suggestions for successful practices in teaching and learning in higher education.
Paper presented at the Regional Conference on Institutionalising Best Practice in Higher Education, UWI, St. Augustine, Trinidad and Tobago, 24-26 June, 2015.
Keywords: Online teaching; Online instructors; Human resources development; Higher education; Training programmes; Open Campus, UWI